Pemberdayaan UMKM Roti Kukus Oh My Sharga Bread Melalui Penguatan Legalitas, Strategi Pemasaran Digital, Dan Tata Kelola Keuangan Berbasis SAK EMKM - Silmi Silmi; Yurniwati Yurniwati; Verni Juita; Rahmat Kurniawan; Fitriyeni Oktavia; Kevry Ramdany; Nadya Putri Nasha; Alya Azilah Ardhani; Naufal Dwi Febiansyah (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting national economic growth; however, many business actors still face challenges related to legality, marketing, and financial management, which affect their competitiveness. One MSME experiencing such issues is “Oh My Sharga Bread” steamed bread. This community service program aims to strengthen business legality, improve digital marketing strategies, and organize financial reporting based on the Micro, Small, and Medium Entity Accounting Standards (SAK EMKM). The mentoring activities included problem identification, technical guidance, facilitation of Business Identification Number (NIB) registration and halal certification, training in financial recording using the SIAPIK application, digital marketing assistance, and redesigning product packaging and logos. The results showed significant achievements: business legality was obtained, financial reports became more structured, and digital marketing expanded market reach. Sales turnover increased by 30%, the number of customers grew by 50 people, and social media engagement rose by 45%. The new packaging and logo design enhanced product image and consumer appeal. The impact of this program goes beyond solving technical problems; it also builds the partner’s capacity to compete in broader and sustainable markets. This activity contributes to achieving the Sustainable Development Goals (SDGs), particularly Goal 8 on decent work and economic growth. Therefore, this mentoring program effectively improves MSME competitiveness and serves as a participatory empowerment model that can be replicated.